Family pets - Shand, Pat (Silver Dragon Books, 2015)
"Ever since her parents died on her fifth birthday, Thomasina has been daydreaming that someday something amazing will happen in her life to make up for the hurt she's been through. But after turning sixteen, Thomasina begins to accept that her life will remain unremarkable. But when she wakes up one morning to discover that her foster family has been turned into pet animals and her favorite pet snake into a dashing young man, her ordinary life will turn into an extraordinary adventure!"--OCLC.